The Effects of Work Autonomy towards Employees Loyalty in Millennial Generation with Work-Life Balance as Mediator - Taufick, Anastasia Laura Kristianto; Kurniawan, Jimmy Ellya (Psychopreneur Journal, 2023)
The active workforce in Indonesia is dominated by the millennial generation. However, millennial employees have a characteristic that tend to be disloyal when their needs are not facilitated. Past researches have shown work-life balance as one of their main needs. Hypothesis of this research is the effects of work autonomy towards employees loyalty in millennial generation with work-life balance as mediator. This is a quantitative research and datas were collected using the work autonomy scale developed by Breaugh (1999), the work-life balance scale developed by Fisher, et al (2009), and the employee loyalty scale developed by Dutta and Dhir (2021). This research is a total population study with 288 respondents from PT MF. The results showed that work-life balance couldn’t moderate the effect of work autonomy on millennial employee loyalty (p>.05), because the majority of respondents were male employees who view work autonomy as a way to develop loyalty and not work-life balance, considering their role as breadwinner for their family.